PENGARUH MEDIA PEMBELAJARAN AUGMENTED REALITY BERBANTU APLIKASI ASSEMBLR TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS V SDN 060826 MEDAN AREA: Penelitian - HERAWATI; Apiek Gandamana; Nurmayani; Laurensia Perangin Angin; Waliyul Maulana Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effectiveness of using Augmented Reality (AR)-based learning media with the AssemblrEdu application in improving students' understanding of Pancasila Education material. Using a quasi-experimental method with a pretest-posttest design, this study compared student learning outcomes in the experimental class using AR media and the control class using conventional methods. The results showed a significant increase in student learning outcomes, with 81.82% of students in the experimental class achieving scores above 70 after using AR media, compared to only 45.46% before learning. The t-test showed a significant difference between the experimental and control classes (significance value 0.000 <0.05). In conclusion, the use of AR media assisted by AssemblrEdu has proven effective in improving students' understanding and learning outcomes, making learning more interesting and interactive, and helping students understand complex material more easily.